2012
DOI: 10.1021/mp200573f
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable Polymer Coated Drug Eluting Stent: A Model Study

Abstract: In drug eluting stent technologies, an increased demand for better control, higher reliability, and enhanced performances of drug delivery systems emerged in the last years and thus offered the opportunity to introduce model-based approaches aimed to overcome the remarkable limits of trial-and-error methods. In this context a mathematical model was studied, based on detailed conservation equations and taking into account the main physical-chemical mechanisms involved in polymeric coating degradation, drug rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…Recent investigations have been working on the development of efficient NO-related materials for clinical demands [5][6][7] . In relation to cardiovascular disease (CVD) therapies, although implants like vascular stents have demonstrated its benefit effects, thrombus formation and intimal hyperplasia are still concerns [6][7][8] . One of the main topics of stent design is 'rapid endothelialization', mainly ascribed to the essentially inherent properties of generating NO via eNOS in the endothelial cell (EC) layer 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have been working on the development of efficient NO-related materials for clinical demands [5][6][7] . In relation to cardiovascular disease (CVD) therapies, although implants like vascular stents have demonstrated its benefit effects, thrombus formation and intimal hyperplasia are still concerns [6][7][8] . One of the main topics of stent design is 'rapid endothelialization', mainly ascribed to the essentially inherent properties of generating NO via eNOS in the endothelial cell (EC) layer 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Biodegradable polymers such as poly(lactic acid) (PLA) and poly(lactic-co-glycolic acid) have also been explored as completely degradable platforms and as stent coatings. 10,11,[23][24][25][26][27] The immobilization of heparin as an anti-coagulant on the surfaces of stent coatings has been employed with the aim of imparting non-thrombogenic properties, and has met with variable success. [28][29][30][31] The conjugation of antibodies aimed at capturing endothelial progenitor cells to promote re-endothelialization are also being explored.…”
mentioning
confidence: 99%
“…The sirolimus and ALA eluted more quickly from SAS than SES and AES because the amount of coating polymer of SAS was less than other stents for same coating thickness. Other study reported that 'with the increase of drug-topolymer ratio, the release rate increases [24,25]. '…”
Section: Evaluation Of Aes Ses and Sasmentioning
confidence: 99%